Brugada Syndrome: Warning of a Systemic Condition? - D'Imperio, Sara; Monasky, Michelle M.; Micaglio, Emanuele; Ciconte, Giuseppe; Anastasia, Luigi; Pappone, Carlo (Frontiers in Cardiovascular Medicine, 2021)
Brugada syndrome (BrS) is a hereditary disorder, characterized by a specific electrocardiogram pattern and highly related to an increased risk of sudden cardiac death. BrS has been associated with other cardiac and non-cardiac pathologies, probably because of protein expression shared by the heart and other tissue types. In fact, the most commonly found mutated gene in BrS, SCN5A, is expressed throughout nearly the entire body. Consistent with this, large meals and alcohol consumption can trigger arrhythmic events in patients with BrS, suggesting a role for organs involved in the digestive and metabolic pathways. Ajmaline, a drug used to diagnose BrS, can have side effects on non-cardiac tissues, such as the liver, further supporting the idea of a role for organs involved in the digestive and metabolic pathways in BrS. The BrS electrocardiogram (ECG) sign has been associated with neural, digestive, and metabolic pathways, and potential biomarkers for BrS have been found in the serum or plasma. Here, we review the known associations between BrS and various organ systems, and demonstrate support for the hypothesis that BrS is not only a cardiac disorder, but rather a systemic one that affects virtually the whole body. Any time that the BrS ECG sign is found, it should be considered not a single disease, but rather the final step in any number of pathways that ultimately threaten the patient’s life. A multi-omics approach would be appropriate to study this syndrome, including genetics, epigenomics, transcriptomics, proteomics, metabolomics, lipidomics, and glycomics, resulting eventually in a biomarker for BrS and the ability to diagnose this syndrome using a minimally invasive blood test, avoiding the risk associated with ajmaline testing.